Novel electrically driven direct-writing methods with managed control on in-situ shape and encapsulation polymer forming - Ahmad, Z; Nangrejo, M; Rasekh, M; Stride, E; Edirisinghe, M (2013)
Electrospraying and electrospinning are amongst the common methods of forming polymeric micro- and nano-scaled structures using electrically driven polymer processing. Utilising a co-axial flow of materials has been successful in enabling encapsulated structures to be generated by these techniques. However, with both of these methods, including their respective co-axial forms, there is limited control over the deposition of the resultant structures. Recently, an electrically driven direct-writing method has been developed which is based upon the same fundamental principles, but with the ability to deposit and form structures in an ordered manner, which has previously been restricted largely to single needle flow processing. In this paper, using selected polymeric materials, we demonstrate two novel methods of this direct-write system. The first method shows how the shape of formed structures can be varied in-situ using a single needle flow direct-write process. Secondly, we demonstrate how co-axial flows can be utilised to write and form encapsulated structures. We envisage that while the use of electrospinning and electrospraying methods will continue to expand, these novel areas will offer much greater control over the forming of a plethora of micro- and nano-scaled structures and will be essential for topographic studies (e. g. of living cells), novel particle preparation methods, coatings and direct writing of polymeric biomaterials. © 2011 Springer-Verlag France.